Clima laboral y su incidencia en la productividad del talento humano del Banco Nacional de Fomento sucursal Santo Domingo de los Tsáchilas en el año 2013 - Salcedo Sarmiento, María Teresa de Jesús (2015)
The present investigation was to determine the National Development Bank, Branch Santo Domingo de los Tsáchilas, if there was a proper human resource management, enabling it to increase performance in both performance; employees and managers, through employment and development of a Procedures Manual Labor Relations, as detailed in the research that was carried out in favor of improving the organizational climate. Consequently, management is key to organizational success in general. The working environment is an issue of great importance today, for all organizations and especially for public and private institutions, which is why we research the following general objective was raised: "To determine the incidence of work climate in the development of human talent National Development Banco Nacional de Fomento Santo Domingo de los Tsáchilas to improve productivity in the institution "the same as we established the organizational assessment of the entity under study; highlighting issues related to job performance of employees of the National Development Banco Nacional de Fomento Santo Domingo de los Tsáchilas . Therefore, the intention is to know the basics of what a weather organizational, the importance of the study and a simple and reliable way to diagnose for any company considering that it will be essential to adapt the variables to be evaluated according to the needs of the organization to achieve success. In order to analyze and propose alternatives for change, then assessed by a SWOT analysis the necessary corrections in improving the implementation of Procedures Manual, which highlight the productivity and performance of all employees and faithfully reflected in the attention to client and its acceptance by the actors. Key words: Procedures Manual, productivity, incidence, working environment